-x+7=-13-3x

Simple and best practice solution for -x+7=-13-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+7=-13-3x equation:


Simplifying
-1x + 7 = -13 + -3x

Reorder the terms:
7 + -1x = -13 + -3x

Solving
7 + -1x = -13 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
7 + -1x + 3x = -13 + -3x + 3x

Combine like terms: -1x + 3x = 2x
7 + 2x = -13 + -3x + 3x

Combine like terms: -3x + 3x = 0
7 + 2x = -13 + 0
7 + 2x = -13

Add '-7' to each side of the equation.
7 + -7 + 2x = -13 + -7

Combine like terms: 7 + -7 = 0
0 + 2x = -13 + -7
2x = -13 + -7

Combine like terms: -13 + -7 = -20
2x = -20

Divide each side by '2'.
x = -10

Simplifying
x = -10

See similar equations:

| -16-9=x | | 3x-11=x-7 | | 8.3=d+4.7 | | 106=-7x | | 21=4x-9-9 | | 3m+2=7m | | h=0.01x^2-x+35 | | -5-11=x | | 5-2c=8 | | 3x-2=11-4 | | 9ln(3x)=36 | | 7x-3y=-12 | | 3u^2-15u=0 | | 6x+4=3(3x-5) | | 180=2x-30+x | | =((18x+12)-(6x+7)) | | 90=2x-30+x | | ((18x+12)-(6x+7))= | | t^2-6t+9= | | 3x^2+4x-13=0 | | -4(1-5b)-3b=-123 | | 6x-3(x+2)=21 | | 4(x+2)-3x+11=2(3x-2)+3(x+4) | | 90=2x-30 | | 2x+6-2x=6 | | 6(3x-5)-8=18x-38 | | -10+2b=-2(b-2)+6 | | x^2+10x+25=75 | | -3x-3=-3+5x | | Z^2+6z-12=0 | | 68x=4600 | | 9-2=-9+1 |

Equations solver categories